2022
DOI: 10.1055/a-1826-0049
|View full text |Cite|
|
Sign up to set email alerts
|

MR Enterography in Crohnʼs Disease: Comparison of Contrast Imaging with Diffusion-weighted Imaging and a special Form of Color Coding

Abstract: Purpose We compared contrast-enhanced MR enterography with diffusion-weighted sequences to evaluate the validity of diffusion-weighted sequences for activity assessment in Crohnʼs disease compared to endoscopy. In addition, we investigated a new color-coded image post-processing technique in comparison with standard sequences and endoscopy. Materials and Methods Included were 197 MR enterographies (2015–2017) performed by using standardized examination protocols. The intestine was divided into 7 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“… T2-sMARIA shows a diagnostic accuracy similar to CE-sMARIA in all of these fields. Jakob, 2022 [43] DWI sequences with color coding ileocolonoscopy small bowel and colon active inflammation adult DWI-based color-coded image: 81.3% Sens, 70.5% Spec DWI Seo score: 87.9% Sens, 71.8% Spec DWI was as good as CE sequences in diagnosing active disease. Color-coding did not add diagnostic value Cococcioni, 2021 [58] CINE quantitative motility histopathology terminal ileum active inflammation pediatric MI was lower in inflamed bowel (median:0.12) compared to normal bowel (median:0.21) ( p = 0.02).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“… T2-sMARIA shows a diagnostic accuracy similar to CE-sMARIA in all of these fields. Jakob, 2022 [43] DWI sequences with color coding ileocolonoscopy small bowel and colon active inflammation adult DWI-based color-coded image: 81.3% Sens, 70.5% Spec DWI Seo score: 87.9% Sens, 71.8% Spec DWI was as good as CE sequences in diagnosing active disease. Color-coding did not add diagnostic value Cococcioni, 2021 [58] CINE quantitative motility histopathology terminal ileum active inflammation pediatric MI was lower in inflamed bowel (median:0.12) compared to normal bowel (median:0.21) ( p = 0.02).…”
Section: Resultsmentioning
confidence: 98%
“…With regard to potential novel technologies utilizing DWI, recent research has indicated that diffusion Kurtosis imaging (DKI) and intravoxel incoherent motion (IVIM) are alternative techniques that may offer higher levels of accuracy than conventional DWI and hold promise for future use [ 41 , 42 ]. Additionally, Jakob et al have employed an innovative color-coding program for DWI images, demonstrating favorable results [43] . Moreover, DWI and ADC mapping have been utilized for detecting fibrostenotic complications, which will be discussed in more detail later.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging was also suggested [ 27 ], but it is not mandatory. Nonetheless, we strongly recommend its use because DWI improves the diagnostic accuracy of MRE [ 28 , 29 , 30 ]. DWI should be acquired in the axial plane during free breathing and must include b values ranging from 0 to 900 [ 26 ].…”
Section: Guidance In Performing Mrementioning
confidence: 99%